Impactos socioambientais na Amazônia: análise das transformações no uso da terra no município de Autazes - AM - Soares, Fidel Vilioni Peixoto (2009)
This study is an analysis of the social and environmental use of the occupation of the land in the riparian forests in municipality of Autazes, Estate of Amazonas, focusing on social environmental impacts produced by these changes, and discusses the changes in the Amazon area through a reading of several interconnected transformation that Amazon comes through. This wok has the titles: Social and environmental impacts in the Amazon: analysis of the changes in land use in Autazes-AM, is an analysis of environmental and social impacts provided by the advances of the agropastorates activities, and among them we can emphasize: deforestation, fires, siltation of the rivers, soil degradation food security, and others. It s also examined the production of the Amazon area in a national, regional and local scale, seeking to context and inter-relate the progress of agriculture and other factors related to changes in land use, and explain the logic of the capitalist mode of production as the propitiator of the environmental and social impacts. In this way, this work seeks to show through context analysis of the Amazon space, more precisely in Autazes-AM, forms of sustainable use of the soil and other environmental resources. Accordingly, this work points to changes in the land use by sustainable economy alternatives means for the inclusion of the Amazon population to reach the conclusions that the way of preservation and conservation is necessary for such reflections